Detection of voltage pulse width effect on charge accumulation in PSCs using EFISHG measurement - Zubair Ahmad; D. Taguchi; Sanghyun Paek; Arti Mishra; Jolly Bhadra; M. Iwamoto; T. Manaka; Mohammad Khaja Nazeeruddin (Results in Physics, 2020)
We report the effect of applied pulse width on charge accumulation in triple cation perovskite solar cells (PSCs) during the Electric Field Induced Second Harmonic Generation (EFISHG) measurements. The PSCs were prepared in the n-i-p structure using the layer-by-layer deposition technique. The triple cation perovskite precursor containing FAPbI3, MAPbBr3, and CsPbI3 was used to make the perovskite layer on the FTO/c-TiO2/mTiO2 substrates. Spiro OMeTAD was used as a hole transport material over the perovskite active layer, followed by the deposition of Au electrodes. The average power conversion efficiency (PCE) of the fabricated PSCs was 19.17 ± 0.02%. The electric field in the PSCs was selectively probed by the fundamental laser beam wavelength of 960 nm during the EFISHG measurements. Two different pulse widths (100 µs and 50 ms) of the applied potential were used in this study, with consideration of electrode charging and interface charging of PSCs. It has been observed that the pulse width of the applied electric field has a significant effect on the charge accumulation in the PSCs. Using the transient EFISHG measurements, it has also been found that the charging & discharging processes reversibly happen. However, the charging & discharging processes are influenced by remained charges at the interface in PSCs in the investigated triple cations PSCs. The EFISHG results can be well explained by using the Maxwell–Wagner model.